Materi (Isi) Kurikulum Bahasa Arab: Teknik, Media, dan Evaluasi Pembelajaran - Imroatus Shalihah,; Ubaid Ridlo ,; Maswani, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the Arabic Language Curriculum Material (Content) in terms of Learning Techniques, Media, and Evaluation. Arabic language learning is a crucial part of Islamic education because it serves as the primary means of understanding religious teachings and broadening scientific and cultural horizons. In its implementation, Arabic language learning cannot be separated from three main components: techniques, media, and evaluation. Learning techniques serve as the teacher's operational steps in effectively implementing methods in the classroom. The success of implementing these techniques depends heavily on the teacher's creativity and ability to adapt learning strategies to the students' conditions. Meanwhile, learning media plays a crucial role as a tool that can attract attention, facilitate understanding, and strengthen students' memory of the material being taught. Learning evaluation serves as a measuring tool to determine the extent to which learning objectives have been achieved. Through evaluation, teachers can assess student success, identify weaknesses in the learning process, and establish corrective measures to enhance Arabic language teaching in the future. Thus, the combination of the application of appropriate techniques, creative use of media, and systematic evaluation will significantly contribute to the success of Arabic language learning. This also demonstrates that teachers have a strategic role as designers and implementers of Arabic language curricula that are oriented towards improving the quality of student learning outcomes.